Adaptabilidad y valor nutricional de las leguminosas kudzú (Pueraria phaseoloides), centrosema (Centrosema acutifolium), mucuna (Mucuna pruriena) en el campo Experimental La Playita UTC – La Mana - Palomo Guanoluisa, Juan José (2015)
The present research "Adaptability and nutritional value of leguminous kudzu (Pueraria phaseoloides), Centrosema (Centrosema acutifolium), Mucuna (Mucuna pruriena) was carried out at the experimental field La Playita CTU – La Maná". The objectives to be reached were: To establish the behavior and productivity of leguminous creepers, to determine the nutritional value of these species. A Complete Randomized Design (CRD) was applied with three treatments and six replications and two plants as experimental unit. The results were: On plant height, fodder biomass, and weight of root in increasing emphasize the leguminous centrosema (82.54 cm, 147.65 and 4.80 g)....